A Novel Construction of Lentiviral Vectors for Eliminating Tumorigenic Cells from Pluripotent Stem Cells. (8th November 2017) - Ide, Kanako; Mitsui, Kaoru; Irie, Rie; Matsushita, Yohei; Ijichi, Nobuhiro; Toyodome, Soichiro; Kosai, Ken‐ichiro
Abstract: The risk of tumor formation poses a challenge for human pluripotent stem cell (hPSC)‐based transplantation therapy. Specific and total elimination of tumorigenic hPSCs by suicide genes (SGs) has not been achieved because no methodology currently exists for testing multiple candidate transgene constructs. Here, we present a novel method for efficient generation of tumorigenic cell‐targeting lentiviral vectors (TC‐LVs) with diverse promoters upstream of a fluorescent protein and SGs. Our two‐plasmid system achieved rapid and simultaneous construction of different TC‐LVs with different promoters. Ganciclovir (GCV) exerted remarkable cytotoxicity in herpes simplex virus thymidine kinase ‐transduced hPSCs, and high specificity for undifferentiated cells was achieved using the survivin promoter (TC‐LV.Surv). Moreover, GCV treatment completely abolished teratoma formation by TC‐LV.Surv‐infected hPSCs transplanted into mice, without harmful effects. Thus, TC‐LV can efficiently identify the best promoter and SG for specific and complete elimination of tumorigenic hPSCs, facilitating the development of safe regenerative medicine. Stem Cells 2018;36:230–239 Abstract : This is a novel system for specific and efficient elimination of tumorigenic cells in transduced human pluripotent stem cells. Optimal expression levels of therapeutic genes are crucial for tumorigenic cell‐specific elimination. Our "TC‐LV" system enables systematic analysis of multiple candidate promoters in order to identify " the most suitable" promoter.